Seasonal climate predictability and forecasting: status and prospects. (14th June 2013) - Doblas‐Reyes, Francisco J.; García‐Serrano, Javier; Lienert, Fabian; Biescas, Aida Pintó; Rodrigues, Luis R. L.
Abstract: Seasonal climate forecasts occupy an intermediate zone between weather forecasting and climate projections. They share with the numerical weather prediction the difficulty of initializing the simulations with a realistic state of the atmosphere and the need to periodically verify different aspects of their quality, while additionally are burdened by uncertainties in feedback processes that also play a central role in constraining climate projections. Seasonal predictions have to deal also with the challenge of initializing all the components of the climate system (ocean, sea ice, and land surface). The value of skilful seasonal forecasts is obvious for many societal sectors and is currently being included in the framework of developing climate services. Seasonal forecasts will in addition be valuable by increasing the acceptance of climate projections among the general public. This advanced‐review article presents an overview of the state‐of‐the‐art in global seasonal predictability and forecasting for climate researchers and discusses fundamental advances to increase forecast quality in the near future. The article concludes with a list of challenges where seasonal forecasting is expected to focus on in the near future. WIREs Clim Change 2013, 4:245–268. doi: 10.1002/wcc.217 This article is categorized under: Climate Models and Modeling > Earth System Models Climate Models and Modeling > Knowledge Generation with Models Social Status of Climate Change Knowledge > Climate Science and Decision Making